An insight into SARS-CoV-2 structure, pathogenesis, target hunting for drug development and vaccine initiatives. Issue 6 (25th February 2022) - Ghosh, Arijit; Kar, Paritosh K.; Gautam, Anupam; Gupta, Rahul; Singh, Rajveer; Chakravarti, Rudra; Ravichandiran, Velayutham; Ghosh Dastidar, Shubhra; Ghosh, Dipanjan; Roy, Syamal
Abstract : The fundamental factors of Covid 19 research. Abstract : SARS-CoV-2, the virus responsible for the COVID-19 pandemic, has been confirmed to be a new coronavirus having 79% and 50% similarity with SARS-CoV and MERS-CoV, respectively. For a better understanding of the features of the new virus SARS-CoV-2, we have discussed a possible correlation between some unique features of the genome of SARS-CoV-2 in relation to pathogenesis. We have also reviewed structural druggable viral and host targets for possible clinical application if any, as cases of reinfection and compromised protection have been noticed due to the emergence of new variants with increased infectivity even after vaccination. We have also discussed the types of vaccines that are being developed against SARS-CoV-2. In this review, we have tried to give a brief overview of the fundamental factors of COVID-19 research like basic virology, virus variants and the newly emerging techniques that can be applied to develop advanced treatment strategies for the management of COVID-19 disease.